Gastro-intestinal parasitism among two swine populations in Malaysia: highlighting the zoonotic transmissible protozoan Balantidium coli infections - Tan, T.K.; Low, V.L.; Lee, S.C.; Chandrawathani, P.; Premaalatha, B.; Lim, Y.A.L. (Department of Veterinary Services Malaysia, 2014)
Limited information is available regarding gastro-intestinal (GI) parasitic infections in Malaysian swine populations. Hence, the present study aims to determine the prevalence of GI parasites in two swine populations in Malaysia, using formalin-ether concentration technique. In the present study, three helminths and two protozoa were detected in 91 swine rectal fecal samples. The zoonotic transmissible protozoan, Balantidium coli (22.0%) had the highest infection rate, followed by strongyle (4.4%), Entamoeba spp. (2.2%), Fasciolopsis spp. (1.1%) and Trichuris suis (1.1%). The co-infection between T. suis and B. coli was also found in this study.